Market Imperfections, Labor Management, and Earnings Differentials in a Developing Country: Theory and Evidence from Yugoslavia - Estrin, Saul; Moore, Robert E.; Svejnar, Jan (Quarterly Journal of Economics, 1988)
In this paper we evaluate empirically the relative importance of two explanations of Yugoslav interindustry income differentials. One explanation, proposed initially by Vanek and Jovicic [1975], stresses capital market imperfections which permit capital rents to be appropriated as workers' incomes. The second explanation points to labor allocation problems under self-management. We first present a critique of the Vanek-Jovicic original formulation and then respecify the problem to permit simultaneous evaluation of the two schools of thought. Results based on two data sets suggest that labor allocation factors and monopoly power rather than capital rents are the main source of Yugoslav earnings dispersion.